2023
DOI: 10.3390/curroncol30050393
|View full text |Cite
|
Sign up to set email alerts
|

Functional State and Rehabilitation of Patients after Primary Brain Tumor Surgery for Malignant and Nonmalignant Tumors: A Prospective Observational Study

Abstract: The aim of this study was to compare the pre- and postoperative function of patients qualifying for resection of malignant and nonmalignant primary brain tumors to determine the relationship among tumor type, function, and the course of rehabilitation after surgery. This single-center, prospective, observational study recruited 92 patients requiring prolonged postoperative rehabilitation during their inpatient stay, who were divided into a nonmalignant tumor group (n = 66) and a malignant tumor group (n = 26).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
0
4
1
Order By: Relevance
“…There are a few studies dealing with the success of rehabilitation of patients with gliomas, while these articles did not show a statistically significant improvement in the rehabilitation outcome [5,6,9]. Krajewski et al described significant outcome measures after rehabilitation, in which they examined benign and malignant brain tumor patients directly after surgery in contrast to our study [7]. Physiotherapy is usually recommended for patients with persisting motor deficits, while the inpatient rehabilitation pathway for glioma patients has not been analyzed after the completion of postoperative RCT in detail as in our study.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…There are a few studies dealing with the success of rehabilitation of patients with gliomas, while these articles did not show a statistically significant improvement in the rehabilitation outcome [5,6,9]. Krajewski et al described significant outcome measures after rehabilitation, in which they examined benign and malignant brain tumor patients directly after surgery in contrast to our study [7]. Physiotherapy is usually recommended for patients with persisting motor deficits, while the inpatient rehabilitation pathway for glioma patients has not been analyzed after the completion of postoperative RCT in detail as in our study.…”
Section: Discussioncontrasting
confidence: 53%
“…Rehabilitation in patients with diffuse gliomas was rarely analyzed in the literature [5][6][7]. Common disorders that require neurooncological rehabilitation include patients with resected astrocytomas especially in cerebral areas with eloquent functionality, because these patients have a higher risk of experiencing neurological deficits such as pareses and neuropsychological deficits.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent prospective study comparing the rehabilitation course of individuals with noncancerous versus cancerous brain tumors, both groups were found to make functional gains despite varying levels of debility preoperatively, suggesting that all patients with brain tumors can benefit from skilled therapy. 16 Although not statistically significant at conventional levels, Black patients tended to be more likely to be discharged to an IRF when compared to white patients (p = .06). A similar racial pattern has been previously noted in other rehabilitation populations such as stroke.…”
Section: Discussionmentioning
confidence: 81%
“…Their effects continue after surgical treatment. Symptoms trigger each other, and more than one symptom disrupts individuals' physical, cognitive, and psychosocial functions in a way that affects daily life [5][6][7]. Many challenges remain in the effective management of symptoms in adults with brain tumors [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many challenges remain in the effective management of symptoms in adults with brain tumors [8]. Patients may become dependent on others before and after surgery [5]. When the caregiver burden studies in caregivers of patients with PBT were reviewed, it was found that the neuropsychological status of the patients [9], activities of daily living [10], and economic inadequacies [11] increase the caregiver burden and cause many problems in caregivers [12].…”
Section: Introductionmentioning
confidence: 99%